Revisiting Lisbon in The Book of Disquiet - Thomas Cousineau (University of Bucharest Review. Literary and Cultural Studies Series, 2016)
This paper explores the strikingly different representations of Pessoa’s native city offered by the lordly cicerone of Pessoa’s guidebook Lisbon: What Every Tourist Should See and the lowly assistant bookkeeper of his modernist masterpiece, The Book of Disquiet. For the cicerone, Lisbon is a magnificent imperial city whose treasures vie with those of other European capitals; for the bookkeeper, it is a neighborhood limited almost exclusively to the Rua dos Douradores, the drab, somewhat louche street where he lives and works. The tedium of his daily life is never relieved by the inspiring sight of a magnificent historical monument or an impressive public square. In place of such touristic attractions, we find frequent mention of such utterly worthless places as the office in which he works, the restaurant in which he meets the stranger, the tavern across the street, the fourth-floor rented room from whose window he gazes, and the barbershop in which he learns of the barber’s death. Despite these differences, however, both Lisbon and The Book fulfill – each in its own distinctive way – the aspiration to which Soares gives voice when he wishes that “there could at least be a paradise made of all this, even if only for me.” As I shall demonstrate here, the cicerone presents Lisbon as a beautiful paradise, made of magnificent things that one need only see in order to admire, while for the bookkeeper it is a rather dismal place that will, however, be rendered sublime by the immense poetic